Pengaruh Harga Gabah terhadap Kesejahteraan Petani di Sumatera Utara pada Tahun 2020-2021 - Satria Abdillah Ilman; Muhammad Syahbudi (El-Mujtama: Jurnal Pengabdian Masyarakat, 2023)
One of the keys to the growth of the agricultural sector is the level of welfare enjoyed by farmers. The purpose of this study is to find out how the welfare of farmers in North Sumatra will be affected by the price of grain in 2020-2021. In accordance with the research design, quantitative descriptive research will be used to conduct this research. This kind of research is quantitative. That secondary data is used. The Central Bureau of Statistics provides information for this (BPS). The data analysis technique used Multiple Linear Regression Test with SPSS application. The results showed that the probability value. Tcount of the dry milled grain variable (X1) is 0.019 < from 0.05 so that the milled dry grain variable has a significant effect on the farmer's exchange rate variable in 2020-2021. The probability value of Tcount of Harvested Dry Grain (X2) is 0.966 > from 0.05 so that the Harvested Dry Grain variable has no effect on the Farmer's Exchange Rate variable (Y) in 2020-2021. The calculated F probability value (sig.) above is 0.047 < from the 0.05 significance level (0.047 < 0.05). So it can be said that the Variables of Milled Dry Grain and Harvested Dry Unhusked Simultaneously have a significant effect on Farmers' Exchange Rates in 2020-2021. Keywords: Welfare, Grain